Peranan Disiplin Kerja Dalam Meningkatkan Kinerja Karyawan Pada PT Permodalan Nasional Madani Cabang Sukatani - Dahlia, Dahlia; Suroso, Suroso; Anggela, Flora Fatricia (STIE AMKOP, 2025)
To determine the role of work discipline in improving employee effectiveness at PT Permodalan Nasional Madani, Suka Tani Branch, this study employed descriptive qualitative research, investigating events or incidents that arise in the field, then analyzing them to finally draw conclusions. Primary data was obtained from the responses of respondents, who served as the sample for the study. Indicators of work discipline are the drive and strength within an individual employee to achieve a specific goal. Essentially, employees who lack self-discipline oppose or disobey company regulations. Weakened work discipline will impact employee morale and the company's progress. Observations and interviews conducted at PT PERMODALAN NASIONAL MADANI indicated a significant decline in employee discipline, as evidenced by data on attendance and lateness. However, the study identified issues such as employee non-compliance with work hour regulations.